Barriers and facilitators of a school-based health promotion program: a qualitative approach - Rodrigues, Filipa (2018)
«Heróis da Fruta – Lanche Escolar Saudável» Project (HF) is a nationwide school-based health promotion program in Portugal developed and coordinated by a multidisciplinary team, including dietitians. The program is implemented by educators and teachers in a school setting, to promote fruit and vegetable consumption among kindergarten and school-aged children. Present research intended to identify and analyze barriers and facilitators recognized by educators and teachers during the implementation of HF. Authors chose semi-structured interview to identify perceptions of 28 educators and teachers. Interviews were transcribed verbatim. Data were coded and analyzed using thematic analyses. Main barriers identified during implementation of HF were time issues (e.g. implementing activities), extra workload and lack of communication. Facilitators were related to ludic-pedagogic activities (e.g. cross-curricular activities), support (e.g. school staff collaboration) and adaptation (e.g. easy to implement). Such results were also identified in previous studies. The research confirms how important is a qualitative approach to adapt an intervention to its context, as it can soothe barriers that might be considered when developing and implementing a school-based health promotion program.